2021
DOI: 10.1128/msystems.00866-21
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Unveils Posidonia oceanica “Banquettes” as a Potential Source of Novel Bioactive Compounds and Carbohydrate Active Enzymes (CAZymes)

Abstract: Posidonia oceanica is a long-living and very slow-growing marine seagrass endemic to the Mediterranean Sea that forms large amounts of leaf material and rhizomes, which can reach the shore and build important banks known as “banquettes.” These banquettes accumulate on the shore, where they can prevent erosion, although they also cause social concern due to their impact on beach use. Furthermore, Posidonia dry material has been considered a source of traditional remedies in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The bioinformatic tools for BGC detection and classification, antiSMASH ( 17 ) and BiG-SCAPE ( 18 ), are used by the majority of metagenome studies and are continuously being improved. Recent applications of antiSMASH and BiG-SCAPE have revealed that there are thousands of undescribed BGCs in soil ( 19 22 ), aquatic ( 23 25 ), wastewater ( 26 ), biocrust ( 27 ), fecal ( 28 ), and host-related environments ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bioinformatic tools for BGC detection and classification, antiSMASH ( 17 ) and BiG-SCAPE ( 18 ), are used by the majority of metagenome studies and are continuously being improved. Recent applications of antiSMASH and BiG-SCAPE have revealed that there are thousands of undescribed BGCs in soil ( 19 22 ), aquatic ( 23 25 ), wastewater ( 26 ), biocrust ( 27 ), fecal ( 28 ), and host-related environments ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The order Myxococcales was also abundant in some samples, although very little is known about their physiology and metabolism in marine environments ( Brinkhoff et al, 2012 ). This order has been associated with organic matter degradation in the seagrass rhizosphere ( Ugarelli et al, 2017 ) and in Posidonia oceanica decaying material ( Rubio-Portillo et al, 2021 ). In soil samples, members of Myxococcales present an aerobic metabolism, although some representatives are anaerobes that respire nitrate or Fe (III) ( Treude et al, 2003 ) and produce a wide range of secondary metabolites ( Reichenbach, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the activities of bioactive substances derived from marine macrophytes, especially that of the seagrasses, have not been thoroughly investigated, due to their great biodiversity [ 13 ]. Recently, research interest has turned towards the characterization of the P. oceanica bioactive components [ 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, P. oceanica leaf dead mass is used for the manufacture of glassware, roof insulation, animal feed, fertilizers, energy production [ 14 , 15 , 18 ] and even the detection of new bioactive compounds after cultivation of their associated microbial community [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research interest has turned towards the characterization of the P. oceanica bioactive components [ 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, P. oceanica leaf dead mass is used for the manufacture of glassware, roof insulation, animal feed, fertilizers, energy production [ 14 , 15 , 18 ] and even the detection of new bioactive compounds after cultivation of their associated microbial community [ 19 ].…”
Section: Introductionmentioning
confidence: 99%